EDUCATIONAL AND PROFESSIONAL PLANS AND ASPIRATIONS OF THOSE IN CHARGE OF CARE AND EDUCATIONAL CENTRES AND FAMILY-RUN CHILDREN’S HOME (ON THE EXAMPLE OF BIAŁA PODLASKA POVIAT) - Ruszkowska, Marzena Urszula (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Research for the purposes of this publication was carried out in Biała Podlaska poviat, which is part of  Lublin province. Its implementation was planned within the framework of the project "Education, levelling developmental and educational deficits of children under the care of family-run children's homes, also the care and educational institutions (on the example of Biała Podlaska poviat)". The diagnostic survey method and the study of individual cases were applied. The survey was based on the author's questionnaire designed for the charges of care and educational institutions and family-run children’s homes as well as the interview questionnaire with the educators of family and institutional institutions. In turn, the study of individual cases involved the use of an observation sheet and interviews with coordinators of the examined care and educational centres, directors of family-run children’s houses. The subject of the article are educational and professional plans of the beneficiaries of institutional and family facilities. Attention was paid to the currently implemented level of education and future educational and occupational plans of these children. The aim of the research was to determine how the educational and professional plans of the charges of various forms of foster care are shaped and what are they conditioned  by?Among the indicators determining the implementation of educational and occupational aspirations  of the examined subjects were environmental factors, i.e. location of the facility or the family-run children's home; personal: willingness and motivation to learn, time spent on homework and learning, age and sex of children under their care, their siblings; in addition, the type of facility in which the examined person is staying, received support and help from educators.